DEVELOPMENT OF ELECTRIC DISCHARGE MACHINING (EDM) USING SOLENOID ACTUATOR FOR EDUCATIONAL PURPOSE - Kushendarsyah Saptaji; Arnaz Asa Sholeh; Gigih Priyandoko; Ignatius Budi Hadisujoto (Universitas Mercu Buana, 2021)
The increasing number of materials with variation in properties, especially hard-to-cut, leads to the need for an advanced machining method to process such material. Electric Discharge Machining (EDM) is one of the advanced machining methods widely used for hard-to-cut alloys. The EDM process uses an electrode as the conductor of electrical current to erode the metal alloys and is supported by other components. Due to EDM's high cost and high energy consumption, developing a low-cost EDM and simpler EDM setup is necessary, especially for educational purposes in laboratory activity. However, the EDM design and setup required to produce the desired “spark” have always been a challenge for researchers and manufacturers. In this research, a small-scale EDM setup was built. A solenoid actuator is used to generate simple mechanical movement. The movement is used to control the gap between the workpiece and the electrode to produce a spark. The solenoid actuator is used because of its low cost and simple mechanism. The proposed EDM setup is successfully fabricated and works appropriately by generating sparks and a hole cavity during the process. There are six cavity holes produced in mild steel workpiece during the experiments with various parameters such as current (5A, 7A, and 10A) and frequency (10 Hz and 20 Hz). The varied parameter shows that the higher current and lower frequency removed more materials. In contrast, the higher frequency produced a better quality of the cavity hole. However, the lack of flushing quality on the material debris during the process results in the formation of excess metals around the edge of the hole.